Analisis Hubungan Pengetahuan dan Keterampilan Petani Nilam di Desa Uete Kecamatan Uluiwoi Kabupaten Kolaka Timur - Said Said; Leni Saleh; Sarty Syarbiah; Endang Sumiratin (Politeknik Kampar, 2025)
This study aims to analyze the relationship between the knowledge and skills of farmers in cultivating patchouli in Uete Village, Uluiwoi District, East Kolaka Regency. The sample size used in this study is 23 patchouli farmers. The method used to obtain the necessary data and information is a questionnaire (survey) distributed to the respondents. The scoring technique used in the questionnaire is the Likert scale with three measurement levels to assess the knowledge and skills of the farmers. The Likert scale used in this study allows the researcher to evaluate the extent to which farmers possess the knowledge and skills needed in patchouli farming. The collected data was then analyzed using the Rank Spearman statistical technique to examine the relationship between the farmers' knowledge and the skills they possess. This technique was chosen because it can measure the relationship between two variables that do not need to be normally distributed and are related. The results show that the farmers' knowledge in patchouli farming can be categorized as high, with a percentage of 73.91%. This indicates that the majority of farmers have a good understanding of how to cultivate patchouli, including the techniques needed to improve patchouli yields. Furthermore, the farmers' skill level is also categorized as skilled, with a percentage of 73.18%. This means that most farmers have the necessary skills to manage patchouli farming effectively. Based on these results, it can be concluded that the knowledge and skills of farmers in Uete Village, Uluiwoi District, East Kolaka Regency are in the high category. Good knowledge positively impacts farmers' skills in patchouli farming, indicating that increasing knowledge can contribute to improving skills. Therefore, the development of better training and education for farmers is crucial to enhancing productivity and the sustainability of patchouli farming in the region.